Adhesive, preparation method and highly weather-resistant polarizer

By adding metal salts and inorganic nanoparticles to the binder, the water resistance and high temperature resistance of the binder in high temperature and high humidity environment are solved, and the high weather resistance and excellent optical properties of the polarizer are achieved.

CN119752358APending Publication Date: 2025-04-04ANHUI WANWEI ADVANCED FUNCTIONAL MEMBRANE MATERIALS RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510047686.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing adhesives have poor water resistance and high temperature resistance in high temperature environments, resulting in shrinkage of the edges of the polarizer and reduced polarization.

Method used

By adding metal salts and inorganic nanoparticles to the binder, the coordination between the metal salts and inorganic nanoparticles is utilized to improve the cross-linking reaction and adhesion of the binder, and enhance its dispersion and stability in the water glue.

Benefits of technology

It significantly improves the high temperature and water resistance of the adhesive, prevents the edges of the polarizer from shrinking, maintains high orientation and excellent optical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005238983010000141
    Figure BDA0005238983010000141
  • Figure BDA0005238983010000151
    Figure BDA0005238983010000151
  • Figure BDA0005238983010000171
    Figure BDA0005238983010000171
Patent Text Reader

Abstract

The invention discloses an adhesive and a preparation method thereof and a highly weather-resistant polaroid, belonging to the technical field of polaroids, wherein the adhesive comprises the following raw materials: modified polyvinyl alcohol powder, deionized water, a cross-linking agent, a metal salt, and inorganic nanoparticles, wherein the modified polyvinyl alcohol powder is added in an amount of 2%-20% of the mass of deionized water, the cross-linking agent is added in an amount of 10%-50% of the mass of the modified polyvinyl alcohol powder, the inorganic nanoparticles are added in an amount of 10%-40% of the mass of the modified polyvinyl alcohol powder, and the metal salt is added in an amount of 0.2-1.2 times of the molar amount of acetoacetyl in the modified polyvinyl alcohol powder, and the present invention adds metal salts and inorganic nanoparticles to the adhesive, and the two interact with each other to improve the bonding force of the adhesive, reduce the water vapor permeability of the adhesive layer to improve the durability of the adhesive layer. Using the adhesive as an adhesive layer, the prepared polaroid will not shrink or fade significantly at the edge under high temperature and high humidity conditions, and has high weather resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polarizers, and in particular relates to an adhesive and a preparation method thereof and a highly weather-resistant polarizer. Background Art

[0002] Polarizer is an indispensable and important component in display panel. Polarizer can only propagate in a specific direction when passing through it through a specific molecular arrangement, thereby realizing the polarization of light, and producing image display in combination with backlight source, liquid crystal or light-emitting diode. With the development of display technology, the application scenarios of display panels are constantly enriched, and the application areas of products are gradually expanding to outdoor large screens, car displays and other aspects. Harsh conditions such as high temperature, high humidity, and high ultraviolet light may exist in product application scenarios. Therefore, a polarizer with excellent durability is required to enable it to perform its original functions under harsh conditions.

[0003] At present, polarizer manufacturers mainly produce iodine-based polarizers, and usually use a wet method to process polyvinyl alcohol optical films as base films. The polyhydroxy structure of polyvinyl alcohol is complexed with dichroic polyiodide ions to form polyvinyl alcohol-iodine complexes. The polarizers produced after stretching and orientation have polarized absorption of visible light in the full band. However, PVA resins are hydrophilic and highly hygroscopic, so polarizers are sensitive to changes in temperature and humidity. PVA molecular chains will relax in high temperature and high humidity environments, and the deterioration of molecular chain orientation will also cause the polyiodide ions complexed with them to become unstable. Therefore, protective films are usually attached to both sides or one side of the polarizer layer through adhesives. On the one hand, the presence of a protective film can block water vapor penetration and improve the moisture resistance of the polarizer. On the other hand, the use of adhesives to bond PVA to high temperature or high temperature and high humidity expansion and small shrinkage materials can inhibit the shrinkage of PVA in harsh environments. Therefore, for water-based adhesives, it is required to have high temperature stability, water resistance, and strong adhesion to the film material. Summary of the invention

[0004] The purpose of the present invention is to provide an adhesive and a preparation method thereof and a highly weather-resistant polarizer, aiming to solve the problems that the existing adhesive has poor water resistance and high temperature and humidity resistance, insufficient protection for the polarizer, resulting in shrinkage of the polarizer edge and reduced polarization degree.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] In a first aspect, the present invention provides an adhesive, wherein the adhesive comprises the following raw materials:

[0007] Modified polyvinyl alcohol powder, deionized water, cross-linking agent, metal salt, inorganic nanoparticles.

[0008] Among them, the added amount of modified polyvinyl alcohol powder is 2%-20% of the mass of deionized water, the added amount of crosslinking agent is 10%-50% of the mass of modified polyvinyl alcohol powder, the added amount of inorganic nanoparticles is 10%-40% of the mass of modified polyvinyl alcohol powder, and the added amount of metal salt is 0.2-1.2 times the molar amount of acetoacetyl in the modified polyvinyl alcohol powder.

[0009] The invention adds appropriate metal salts and inorganic nanoparticles into the adhesive and utilizes the coordination effect between the metal salts and the inorganic nanoparticles to improve the reaction degree between the crosslinking agent and the acetoacetyl-modified polyvinyl alcohol on the one hand and improve the bonding force of the adhesive on the other hand. In addition, the coordination effect between the metal salts and the inorganic nanoparticles also enables the inorganic nanoparticles to have better dispersibility in the hydrogel, and the prepared hydrogel has good high temperature resistance and water resistance.

[0010] Furthermore, the modified polyvinyl alcohol powder is acetoacetyl-modified polyvinyl alcohol powder, the degree of substitution of acetoacetyl in the modified polyvinyl alcohol powder is 0.5 mol%-30 mol%, and the cross-linking agent mainly reacts with the highly reactive α-H on the acetoacetyl group to form a cross-linked structure with PVA to obtain a water-resistant adhesive. If the acetoacetyl content is too low, the water resistance of the adhesive will be significantly reduced, and if the acetoacetyl content is too high, there may be a problem of poor compatibility with other reagents, and it is also not applicable.

[0011] Furthermore, if the amount of the inorganic nanoparticles added is too low, the performance of the adhesive will not be significantly improved. If the amount is too high, the uniformity of the glue may deteriorate due to insufficient metal cation complexation and nanoparticle precipitation. Preferably, the amount of the inorganic nanoparticles added is 20%-30% of the mass of the modified polyvinyl alcohol powder.

[0012] Furthermore, the type of the cross-linking agent is not particularly limited, and can be one of aldehyde compounds, amine compounds and melamine compounds, or a plurality of compounds that do not chemically react with each other.

[0013] Furthermore, the aldehyde compound is at least one of formaldehyde, acetaldehyde, glyoxal and glutaraldehyde.

[0014] Furthermore, the amine compound is at least one of ethylenediamine, hexamethylenediamine and polyethyleneimine.

[0015] Furthermore, the melamine compound is methylol melamine and / or methylated methylol melamine.

[0016] Furthermore, the inorganic nanoparticles are spherical nanoparticles with a particle size of 10nm-100nm, preferably 10nm-40nm.

[0017] Furthermore, the inorganic nanoparticles are at least one of spherical nano-silicon dioxide, spherical nano-titanium dioxide, spherical nano-zirconia, spherical nano-zinc oxide and spherical nano-aluminum oxide. In particular, spherical nano-titanium dioxide, spherical nano-zirconia and spherical nano-zinc oxide can give the adhesive excellent anti-ultraviolet effect.

[0018] The inorganic nanoparticles in the present invention are spherical and have a large specific surface area. Under the action of van der Waals forces, the adhesion between the adhesive and the film interface can be improved. At the same time, the spherical nanoparticles and their secondary aggregates can be better embedded in the defects on the surface of the adhesive layer, play a wedging role, and further improve the adhesion. In addition, since the nanoparticles fill the gaps on the surface of the adhesive layer, they can play a blocking role, further reducing the water vapor permeability of the material. Combined with the presence of nanoparticles, the effect of extending the path of water vapor entering the PVA layer is improved, and the moisture resistance of the polarizer is improved. The components in the adhesive exist in the form of nanoparticle-metal ion-PVA complexes. The high temperature stability of metal ions and nanoparticles improves the high temperature resistance of the adhesive, maintains strong adhesion at high temperatures, inhibits PVA retraction, and maintains high orientation; as spherical nanoparticles, the small particle size weakens the scattering effect of light, so at the amount added by the invention, it has no effect on the transmittance of the polarizer.

[0019] Furthermore, the metal salt is at least one of sulfate, chloride and acetate.

[0020] Furthermore, the metal cation in the metal salt is Al 3+ Mg 2+ 、Zn 2+ 、Zr 4+ 、T i 4+ At least one of .

[0021] Furthermore, if the amount of the metal salt added is too high or too low, the water resistance of the adhesive will deteriorate. If the amount added is too low, the dispersibility of the nanoparticles will decrease, which is not conducive to the stability of the system.

[0022] One of the functions of the metal cation in the present invention is to complex with the oxygen atom of the acetoacetyl group on the modified polyvinyl alcohol molecular chain. As an electron-withdrawing group, the electron cloud can be further biased away from the α-H direction, promote the exposure of the α-H hydroxyl group on the acetoacetyl group, reduce the reaction steric hindrance, and promote the reaction between the crosslinking agent and the modified polyvinyl alcohol. More importantly, the presence of the metal ion can form a complex with the oxygen element in the nanoparticles, and the oxygen in the nanoparticles is complexed with the metal ions uniformly dispersed in the modified polyvinyl alcohol solution, promoting the dispersion of the nanoparticles in the adhesive. The uniform dispersion of the nanoparticles in the adhesive makes the adhesive have storage properties and long-term online production properties.

[0023] In addition, due to the active oxygen atoms on the surface of inorganic nanoparticles, most of the untreated nanoparticles are hydrophilic. After complexing with metal ions, the activity of oxygen atoms on the surface of nanoparticles decreases, and it is not easy to combine with other atoms to form hydroxyl functional groups, which is beneficial to improve the moisture resistance of the adhesive. The covalent bond -O-M1-O-M2- formed between the nanoparticles and the modified polyvinyl alcohol makes the nanoparticles and the adhesive connected not only by van der Waals force, but also by chemical bonds, which improves the cohesive force of the adhesive.

[0024] In a second aspect, the present invention also provides a method for preparing the above-mentioned adhesive, comprising the following steps:

[0025] At a temperature of 20°C-35°C, the modified polyvinyl alcohol powder is added to deionized water, stirred for 0.5h-1h, then the temperature is raised to 85°C-95°C for 1h-5h, and the temperature is kept stirred for 1h-5h; then the temperature is lowered to 20°C-35°C for 5h-15h, a metal salt is added and stirred for 0.5h-2h, a cross-linking agent is added, and stirring is continued for 0.5h-3h, and inorganic nanoparticles are added and stirring is continued for 1h-3h to obtain the adhesive.

[0026] In the process of preparing the adhesive of the present invention, the order of adding the crosslinking agent, the metal salt and the inorganic nanoparticles is crucial, and the metal salt should be added first, then the crosslinking agent, and finally the nanoparticles. In order to have better reactivity, the metal salt needs to be added in advance, and the crosslinking agent is added when the metal cations are evenly dispersed after complete dissolution, otherwise the reaction efficiency of the crosslinking agent and the modified polyvinyl alcohol will be reduced. The nanoparticles need to be added last to prevent the nanoparticles from having poor dispersibility after entering the system and causing coagulation, and to prevent the metal salt ions from complexing with the oxygen atoms in the nanoparticles first instead of the oxygen atoms in the acetoacetyl group, thereby failing to effectively improve the reactivity of α-H.

[0027] In a third aspect, the present invention further provides a highly weather-resistant polarizer, comprising a polarizer, an adhesive layer being arranged on both sides of the polarizer, and protective films being arranged on both sides of the adhesive layer away from the polarizer, wherein the adhesive layer is obtained by coating and curing the above-mentioned adhesive.

[0028] Furthermore, the thickness of the adhesive layer is 200nm-600nm.

[0029] Beneficial effects of the present invention:

[0030] The present invention adds metal salts and inorganic nanoparticles to the adhesive, utilizes the complexation of metal cations, inorganic nanoparticles and oxygen atoms in acetoacetylated modified PVA, and improves the high temperature resistance of the adhesive. At the same time, the spherical inorganic nanoparticles can be embedded in the defects on the surface of the adhesive layer or fill the gaps, thereby improving the adhesion of the adhesive, reducing the water vapor permeability of the adhesive layer, and improving the durability of the adhesive layer. At the same time, the complexation of metal cations and oxygen atoms in the nanoparticles can improve the dispersibility of the inorganic nanoparticles in the adhesive, avoid agglomeration and sedimentation, so that the adhesive containing the nanoparticles is easy to store and has the ability to be produced online for a long time.

[0031] The present invention uses an adhesive containing metal salts and inorganic nanoparticles as an adhesive layer. The prepared polarizer does not significantly shrink or fade at the edge of the polarizer under high temperature and high humidity conditions, and has high weather resistance. DETAILED DESCRIPTION

[0032] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0033] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0034] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. For example, without departing from the scope of the implementation regulations of this application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0035] The terms used in the embodiments of the present application are only for the purpose of describing specific implementation rules, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the implementation rules of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0036] It should be understood that in the various embodiments of the present application, the size of the serial number of each process does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the implementation regulations of this application.

[0037] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0038] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0039] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0040] In a first aspect, an embodiment of the present application provides an adhesive, wherein the adhesive comprises the following raw materials:

[0041] Modified polyvinyl alcohol powder, deionized water, cross-linking agent, metal salt, inorganic nanoparticles.

[0042] In some embodiments, the modified polyvinyl alcohol powder is added in an amount of 2%-20% of the mass of deionized water. In the exemplary embodiment, it can be a typical but non-limiting addition amount such as 2%, 5%, 7%, 10%, 12%, 15%, 20%, or a range between any two addition amounts.

[0043] In some embodiments, the amount of the crosslinking agent added is 10%-50% of the mass of the modified polyvinyl alcohol powder. In the exemplary embodiments, it can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% and other typical but non-limiting addition amounts or a range between any two addition amounts.

[0044] In some embodiments, the amount of inorganic nanoparticles added is 10%-40% of the mass of the modified polyvinyl alcohol powder. In the exemplary embodiment, it can be 10%, 15%, 20%, 25%, 30%, 35%, 40% and other typical but non-limiting addition amounts or a range between any two addition amounts.

[0045] In some embodiments, the amount of metal salt added is 0.2-1.2 times the molar amount of acetoacetyl in the modified polyvinyl alcohol powder. In the exemplary embodiment, it can be 0.2 times, 0.5 times, 1.0 times, 1.2 times, etc., typical but non-limiting addition amounts, or a range between any two addition amounts. In this case, the addition of metal salt will not introduce deterioration in the water resistance of the adhesive, and can also keep the inorganic nanoparticles evenly dispersed, which is beneficial to the stability of the system.

[0046] In some embodiments, the modified polyvinyl alcohol powder is acetoacetyl-modified polyvinyl alcohol powder, and the degree of substitution of acetoacetyl in the modified polyvinyl alcohol powder is 0.5 mol%-30 mol%.

[0047] In some embodiments, the inorganic nanoparticles are added in an amount of 20%-30% of the mass of the modified polyvinyl alcohol powder. In exemplary embodiments, the amount may be 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, or any other typical but non-limiting amount or a range between any two amounts. In this case, the inorganic nanoparticles significantly improve the performance of the adhesive, and the adhesive has good uniformity.

[0048] In some embodiments, the cross-linking agent is one of an aldehyde compound, an amine compound, and a melamine compound, or a plurality of compounds that do not chemically react with each other.

[0049] Furthermore, the aldehyde compound is at least one of formaldehyde, acetaldehyde, glyoxal and glutaraldehyde.

[0050] Furthermore, the amine compound is at least one of ethylenediamine, hexamethylenediamine and polyethyleneimine.

[0051] Furthermore, the melamine compound is methylol melamine and / or methylated methylol melamine.

[0052] In some embodiments, the inorganic nanoparticles are spherical nanoparticles with a particle size of 10 nm-100 nm, preferably 10 nm-40 nm.

[0053] In some embodiments, the inorganic nanoparticles are at least one of spherical nano-silicon dioxide, spherical nano-titanium dioxide, spherical nano-zirconia, spherical nano-zinc oxide and spherical nano-alumina. In particular, spherical nano-titanium dioxide, spherical nano-zirconia and spherical nano-zinc oxide can give the adhesive excellent anti-ultraviolet effect.

[0054] In some embodiments, the metal salt is at least one of a sulfate, a chloride, and an acetate.

[0055] In some embodiments, the metal cation in the metal salt is Al 3+ Mg2+ 、Zn 2+ 、Zr 4+ 、T i 4+ At least one of .

[0056] A second aspect of the present application provides a method for preparing the above-mentioned adhesive, comprising the following steps:

[0057] At a temperature of 20°C-35°C, the modified polyvinyl alcohol powder is added to deionized water, stirred for 0.5h-1h, then the temperature is raised to 85°C-95°C for 1h-5h, and the temperature is kept stirred for 1h-5h; then the temperature is lowered to 20°C-35°C for 5h-15h, a metal salt is added and stirred for 0.5h-2h, a cross-linking agent is added, and stirring is continued for 0.5h-3h, and inorganic nanoparticles are added and stirring is continued for 1h-3h to obtain the adhesive.

[0058] A third aspect of an embodiment of the present application provides a highly weather-resistant polarizer, the polarizer comprising a polarizer, adhesive layers are provided on both sides of the polarizer, and protective films are provided on both sides of the adhesive layer away from the polarizer, wherein the adhesive layer is obtained by coating and curing the above-mentioned adhesive.

[0059] In some embodiments, the method for preparing the highly weather-resistant polarizer comprises the following steps:

[0060] S1, swelling the polyvinyl alcohol film in a swelling tank filled with deionized water at 23°C, and stretching the film at a ratio of 1.1 times in the supply direction;

[0061] S2, immersing the obtained film material in an aqueous solution containing elemental iodine and potassium iodide to perform dyeing and stretching, wherein the stretching is performed at a ratio of 1.8 times in the length direction to obtain a dyed optical film;

[0062] S3, immersing the dyed optical film in a boric acid aqueous solution and stretching it to twice the original length, then immersing it in a first solution and stretching it to 5.5 times the original length, and then immersing it in a second solution and stretching it to 5.75 times the original length;

[0063] S4, drying to obtain polarized light with a thickness of 22 μm;

[0064] S5. Apply adhesive on both sides of the polarizer, then attach a protective film, dry to obtain an intermediate product with an adhesive layer, and finally perform heat treatment to obtain the highly weather-resistant polarizer.

[0065] In some embodiments, the thickness of the polyvinyl alcohol film is 60 μm, and the average polymerization degree of polyvinyl alcohol used in the polyvinyl alcohol film is 2600 and the saponification degree is ≥99.9%.

[0066] In some embodiments, in the aqueous solution containing elemental iodine and potassium iodide, the mass fraction of elemental iodine is 0.04%, and the mass fraction of potassium iodide is 2%.

[0067] In some embodiments, the temperature of the boric acid aqueous solution is 30° C., and the mass fraction of boric acid is 3 wt %.

[0068] In some embodiments, the temperature of the first solution is 60° C., and the first solution is composed of boric acid, potassium iodide, and deionized water in a mass ratio of 2:2:100.

[0069] In some embodiments, the temperature of the second solution is 23° C., and the second solution is composed of boric acid, potassium iodide, and deionized water in a mass ratio of 1:5:100.

[0070] In some embodiments, the coating method is one of a casting method, a Meyer rod coating method, a gravure coating method, a comma coating method, a doctor blade coating method, a die coating method, a dip coating method and a spray method.

[0071] In some embodiments, the drying temperature is 30° C.-90° C., and the drying time is 160s-800s.

[0072] In some embodiments, the thickness of the adhesive layer is 200nm-600nm. In exemplary embodiments, the thickness can be 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, etc., typical but non-limiting thicknesses, or a range between any two thicknesses.

[0073] In some embodiments, the heat treatment temperature is 28° C.-45° C., and the heat treatment time is 10 h-500 h.

[0074] The following describes the invention in conjunction with specific embodiments.

[0075] Example 1

[0076] A method for preparing an adhesive comprises the following steps:

[0077] At a temperature of 30°C, 7g of modified polyvinyl alcohol powder was added to 100g of deionized water, and the temperature was raised under program control after stirring for 0.5h. The temperature was raised to 92°C for 2h and stirred for 3h. The temperature was then lowered to 30°C for 5h, 0.9g of metal salt was added and stirred for 1.5h, 2.1g of hexahydroxymethyl melamine was added and stirred for 2h, 1.75g ​​of inorganic nanoparticles were added while stirring, and stirring was continued for 2h to obtain the adhesive.

[0078] The substitution degree of acetoacetyl in the modified polyvinyl alcohol powder is 5 mol%, the metal salt is zinc sulfate, and the inorganic nanoparticles are spherical zinc oxide with a particle size of 20 nm.

[0079] Example 2

[0080] A method for preparing an adhesive comprises the following steps:

[0081] At a temperature of 20°C, 7g of modified polyvinyl alcohol powder was added to 100g of deionized water, and the temperature was raised under program control after stirring for 0.8h. The temperature was raised to 95°C for 1h and stirred for 1h. The temperature was then lowered to 20°C for 8h, 0.26g of metal salt was added and stirred for 0.5h, 2.1g of hexahydroxymethyl melamine was added and stirred for 0.5h, 1.75g ​​of inorganic nanoparticles were added while stirring, and stirring was continued for 3h to obtain the adhesive.

[0082] The substitution degree of acetoacetyl in the modified polyvinyl alcohol powder is 5 mol%, the metal salt is zinc sulfate, and the inorganic nanoparticles are spherical zinc oxide with a particle size of 20 nm.

[0083] Example 3

[0084] A method for preparing an adhesive comprises the following steps:

[0085] At a temperature of 35°C, 7g of modified polyvinyl alcohol powder was added to 100g of deionized water, and the temperature was raised by program control after stirring for 1h, and the temperature was raised to 95°C for 5h, and the temperature was kept stirred for 5h; then the temperature was lowered to 25°C for 10h, 1.54g of metal salt was added, and the mixture was stirred for 2h, 2.1g of hexahydroxymethyl melamine hexamethyl ether was added, and the stirring was continued for 3h, 1.75g ​​of inorganic nanoparticles were added while stirring, and the stirring was continued for 1h to obtain the adhesive.

[0086] The substitution degree of acetoacetyl in the modified polyvinyl alcohol powder is 5 mol%, the metal salt is zinc sulfate, and the inorganic nanoparticles are spherical zinc oxide with a particle size of 20 nm.

[0087] Example 4

[0088] A method for preparing an adhesive, compared with Example 1, the difference is that the amount of inorganic nanoparticles added is different, as shown in Table 1.

[0089] Example 5

[0090] A method for preparing an adhesive, compared with Example 1, the difference is that the amount of inorganic nanoparticles added is different, as shown in Table 1.

[0091] Example 6

[0092] A method for preparing an adhesive, compared with Example 1, the difference lies in that the type of inorganic nanoparticles and the primary particle size are different, as shown in Table 1.

[0093] Example 7

[0094] A method for preparing an adhesive, compared with Example 1, the difference lies in that the type of inorganic nanoparticles and the primary particle size are different, as shown in Table 1.

[0095] Example 8

[0096] A method for preparing an adhesive, compared with Example 1, the difference lies in that the type of inorganic nanoparticles and the primary particle size are different, as shown in Table 1.

[0097] Example 9

[0098] A method for preparing an adhesive, compared with Example 1, the difference lies in that the type of inorganic nanoparticles and the primary particle size are different, as shown in Table 1.

[0099] Example 10

[0100] A method for preparing an adhesive, compared with Example 1, the difference is that the type of metal salt and the amount of metal salt added are different, as shown in Table 1.

[0101] Embodiment 11

[0102] A method for preparing an adhesive, compared with Example 1, the difference is that the type of metal salt and the amount of metal salt added are different, as shown in Table 1.

[0103] Example 12

[0104] A method for preparing an adhesive, compared with Example 1, the difference is that the type of metal salt and the amount of metal salt added are different, as shown in Table 1.

[0105] Embodiment 13

[0106] A method for preparing an adhesive, compared with Example 1, the difference is that the type of metal salt and the amount of metal salt added are different, as shown in Table 1.

[0107] Comparative Example 1

[0108] A method for preparing an adhesive comprises the following steps:

[0109] At a temperature of 30° C., 7 g of modified polyvinyl alcohol powder was added to 100 g of deionized water, and the mixture was stirred for 0.5 h, and then the temperature was raised under program control to 92° C. in 2 h, and the mixture was kept stirred for 3 h; the temperature was then lowered to 30° C. in 5 h, 2.1 g of hexahydroxymethyl melamine was added, and stirring was continued for 2 h to obtain the adhesive.

[0110] Comparative Example 21

[0111] A method for preparing an adhesive comprises the following steps:

[0112] At a temperature of 30°C, 7 g of modified polyvinyl alcohol powder was added to 100 g of deionized water, and the temperature was raised under program control after stirring for 0.5 h. The temperature was raised to 92°C after 2 h, and the temperature was kept stirred for 3 h. The temperature was then lowered to 30°C after 5 h, 2.1 g of hexahydroxymethyl melamine was added, and stirring was continued for 2 h. 1.75 g of inorganic nanoparticles were added while stirring, and stirring was continued for 2 h to obtain the adhesive.

[0113] The substitution degree of acetoacetyl in the modified polyvinyl alcohol powder is 5 mol%, and the inorganic nanoparticles are spherical zinc oxide with a particle size of 20 nm.

[0114] Comparative Example 22

[0115] A method for preparing an adhesive comprises the following steps:

[0116] At a temperature of 30°C, 7g of modified polyvinyl alcohol powder was added to 100g of deionized water, and the temperature was raised by program control after stirring for 0.5h. The temperature was raised to 92°C for 2h and stirred for 3h. The temperature was then lowered to 30°C for 5h, 0.9g of metal salt was added and stirred for 1.5h, 2.1g of hexahydroxymethyl melamine was added, and stirring was continued for 2h to obtain the adhesive.

[0117] The degree of substitution of acetoacetyl in the modified polyvinyl alcohol powder is 5 mol%, the metal salt is zinc sulfate, and the inorganic nanoparticles are spherical zinc oxide with a particle size of 20 nm.

[0118] Comparative Example 3

[0119] A method for preparing an adhesive, compared with Example 1, the difference is that the amount of metal salt added is different, as shown in Table 1.

[0120] Comparative Example 4

[0121] A method for preparing an adhesive, compared with Example 1, the difference is that the amount of metal salt added is different, as shown in Table 1.

[0122] Comparative Example 5

[0123] A method for preparing an adhesive, compared with Example 1, the difference is that the amount of inorganic nanoparticles added is different, as shown in Table 1.

[0124] Comparative Example 6

[0125] A method for preparing an adhesive, compared with Example 1, the difference is that the amount of inorganic nanoparticles added is different, as shown in Table 1.

[0126] Comparative Example 7

[0127] A method for preparing an adhesive, compared with Example 8, the difference is that the inorganic nanoparticle raw materials and shapes are different, as shown in Table 1.

[0128] Comparative Example 8

[0129] A method for preparing an adhesive, wherein the adhesive components and proportions are the same as those in Example 1, but the order of adding the metal salt and the inorganic nanoparticles is changed, and the specific steps are as follows:

[0130] At a temperature of 30°C, 7g of modified polyvinyl alcohol powder was added to 100g of deionized water, and the temperature was raised by program control after stirring for 0.5h. The temperature was raised to 92°C for 2h and stirred for 3h. The temperature was then lowered to 30°C for 5h, and 1.75g ​​of inorganic nanoparticles were added while stirring. The stirring was continued for 2h. 0.9g of metal salt was added and stirred for 1.5h. 2.1g of hexahydroxymethylmelamine was added and stirred for 2h to obtain the adhesive.

[0131] The substitution degree of acetoacetyl in the modified polyvinyl alcohol powder is 5 mol%, the metal salt is zinc sulfate, and the inorganic nanoparticles are spherical zinc oxide with a particle size of 20 nm.

[0132] Comparative Example 9

[0133] A method for preparing an adhesive, wherein the adhesive components and proportions are the same as those in Example 1, but the order of adding the metal salt and the inorganic nanoparticles is changed, and the specific steps are as follows:

[0134] At a temperature of 30°C, 7g of modified polyvinyl alcohol powder was added to 100g of deionized water, and the temperature was raised by program control after stirring for 0.5h, and the temperature was raised to 92°C for 2h, and the temperature was kept stirred for 3h; then the temperature was lowered to 30°C for 5h, 1.75g ​​of inorganic nanoparticles were added while stirring, and stirring was continued for 2h, 2.1g of hexahydroxymethyl melamine hexmethoxy ether was added, and stirring was continued for 2h, and 0.9g of metal salt was added and stirred for 1.5h to obtain the adhesive.

[0135] The substitution degree of acetoacetyl in the modified polyvinyl alcohol powder is 5 mol%, the metal salt is zinc sulfate, and the inorganic nanoparticles are spherical zinc oxide with a particle size of 20 nm.

[0136] Table 1 Raw material components and proportions in adhesives of Examples 1-13 and Comparative Examples 1-7

[0137]

[0138]

[0139] (I) The adhesives obtained from Examples 1 to 13 and Comparative Examples 1 to 9 were tested for stability, and the test process was as follows:

[0140] Each group of adhesives was placed in a water-based adhesive storage tank and allowed to stand. After the preparation was completed and after standing for 24 hours, 10 g of sample was taken out through the sampling port in the middle of the storage tank to test the initial solid content (S) and the solid content after standing for 24 hours (S 24h ), 5 parallel samples were measured at 2g / sample, and the solid content was measured at 105°C for 4h. The test results are shown in Table 2;

[0141] (II) Using the adhesives obtained in Examples 1 to 13 and Comparative Examples 1 to 9, a highly weather-resistant polarizer was prepared. The specific preparation process is as follows:

[0142] S1, a polyvinyl alcohol film with a thickness of 60 μm is swollen in a swelling tank filled with deionized water at 23° C., and stretched at a ratio of 1.1 times in the supply direction;

[0143] S2, immersing the obtained film material in an aqueous solution containing iodine and potassium iodide for dyeing and stretching, wherein the mass fraction of iodine is 0.04%, the mass fraction of potassium iodide is 2%, and the stretching is 1.8 times the ratio in the length direction to obtain a dyed optical film;

[0144] S3, immersing the dyed optical film in a 3 wt % boric acid aqueous solution at 30° C. and stretching it to twice its original length, then immersing it in a first solution and stretching it to 5.5 times its original length, and then immersing it in a second solution and stretching it to 5.75 times its original length;

[0145] S4, drying to obtain polarized light with a thickness of 22 μm;

[0146] S5. Apply adhesive on both sides of the polarizer, then attach a protective film, dry at 60° C. for 500 seconds to obtain an intermediate product with a 400 nm adhesive layer, and finally heat treat at 35° C. for 72 hours to obtain the highly weather-resistant polarizer.

[0147] The temperature of the first solution is 60°C, and the first solution consists of boric acid, potassium iodide and deionized water in a mass ratio of 2:2:100. The temperature of the second solution is 23°C, and the second solution consists of boric acid, potassium iodide and deionized water in a mass ratio of 1:5:100.

[0148] The optical performance test of the polarizer is carried out as follows:

[0149] The polarizer obtained above was cut into a size of 30 mm × 30 mm, and treated at 105°C for 500 h and 65°C / 95% humidity for 500 h, respectively. The polarization degree (P) and monomer transmittance (Ts) of the polarizer were measured in the range of 380 nm-780 nm using a spectrophotometer ("V-7100" manufactured by JASCO, Japan). The sample was measured 10 times and the separation distance between PVA and TAC (protective film) and the fading of the PVA edge were reported as the average value.

[0150] The adhesive bonding performance test of the polarizer is as follows:

[0151] Polaroids may have insufficient high-temperature adhesion of the glue and shrinkage of PVA at high temperatures, causing the PVA edge to separate from TAC. PVA edges may also fade under high temperature and high humidity. Cut each set of polaroids into 200mm×180mm, attach them to a glass plate, and treat them at 105℃ for 500h and 65℃ / 95% humidity for 500h. Use a gantry image tester to test the separation distance between PVA and TAC (L1) and the fading distance of the PVA edge (L2) to evaluate the high temperature and high humidity resistance of the water-based glue. The larger value of the separation distance and fading distance in the optical axis direction and the perpendicular direction is reported as the test result;

[0152] The test results are shown in Table 2;

[0153] Table 2 Test results of adhesives and polarizers of Examples 1-13 and Comparative Examples 1-9

[0154]

[0155]

[0156] Note: No fading was observed at the edges of each group of polarizers under the condition of 105℃ / 500h, that is, there is no L2 value.

[0157] From the test data in Table 2, it can be seen that the initial solid content of the adhesive obtained in Examples 1 to 13 is 9.67%-11.35%, and the solid content after standing for 24 hours is 9.67%-11.32%, with a small difference, indicating that the adhesive prepared by the present invention has good stability, and the nanoparticles are not easy to settle. After high-temperature treatment at 105°C for 500 hours, the monomer transmittance (Ts) of the polarizer is 42.72%-42.86%, and the polarization degree (P) is 99.935%-99.949%, which is slightly different from the monomer transmittance and polarization degree (P) of the original sample. The separation distance (L1) between PVA and TAC is 9 7μm-105μm, the separation distance is small, and after being treated at 65℃ / 95% humidity for 500h, the monomer transmittance (Ts) of the polarizer is 42.69%-42.82%, the polarization degree (P) is 99.979%-99.989%, the separation distance between PVA and TAC (L1) is 62-68μm, and the PVA edge fading distance (L2) is 79-89μm. Compared with the original sample, the changes in monomer transmittance (Ts) and polarization degree (P), the separation distance between PVA and TAC (L1), and the PVA edge fading distance (L2) are all small, indicating that the prepared polarizer has high weather resistance.

[0158] It can be seen from the test results of Example 1 and Comparative Example 1 that the addition of metal salts and inorganic nanoparticles helps to improve the high temperature resistance and high temperature and high humidity resistance of the glue, so that the optical properties of the polarizer are better maintained. After treatment at high temperature, high adhesion is maintained to inhibit PVA shrinkage. The glue has strong moisture resistance. After high temperature and high humidity treatment, the shrinkage distance of PVA is much lower than that of the group without addition, and the fading distance of the PVA edge is short.

[0159] It can be seen from the test results of Example 1 and Comparative Example 21 that the lack of metal salt will cause a significant change in the solid content of the adhesive before and after 24 hours, the sedimentation of nanoparticles, a significant decrease in the stability of the adhesive, and under high temperature conditions and high temperature and high humidity conditions, the optical properties and adhesive adhesion and high temperature and high humidity resistance will deteriorate to varying degrees.

[0160] It can be seen from the test results of Example 1 and Comparative Example 22 that the absence of inorganic nanoparticles will result in poor optical performance of the polarizer and reduced weather resistance.

[0161] It can be seen from the test results of Example 2 and Comparative Example 3 that when the molar ratio of the metal salt to the acetoacetyl group in the modified polyvinyl alcohol is lower than 0.2, the stability of the adhesive is significantly reduced, and the weather resistance of the polarizer under different conditions is also deteriorated to varying degrees.

[0162] It can be seen from the test results of Example 3 and Comparative Example 4 that when the molar ratio of the metal salt to the acetoacetyl group in the modified polyvinyl alcohol is higher than 1.2, the weather resistance of the polarizer under different conditions deteriorates to varying degrees.

[0163] It can be seen from the test results of Example 4, Comparative Example 5 and Comparative Example 1 that when the inorganic nanoparticle additive is less than 10% of the modified polyvinyl alcohol powder, the weather resistance of the polarizer is not significantly improved due to the low addition amount.

[0164] It can be seen from the test results of Example 5 and Comparative Example 6 that when the inorganic nanoparticle additive is higher than 40% of the modified polyvinyl alcohol powder, the stability of the adhesive is significantly deteriorated, and the weather resistance of the polarizer under different conditions is also deteriorated to a certain extent.

[0165] It can be seen from the test results of Example 8 and Comparative Example 7 that when the inorganic nanoparticles are changed from spherical to rod-shaped, the stability of the adhesive is significantly deteriorated, and the weather resistance of the polarizer under different conditions is also deteriorated to a certain extent.

[0166] It can be seen from the test results in Example 1, Comparative Example 8 and Comparative Example 9 that by changing the order of adding the cross-linking agent, the metal salt and the inorganic nanoparticles, the stability of the adhesive is significantly deteriorated, and the weather resistance of the polarizer under different conditions is also deteriorated to a certain extent.

[0167] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0168] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An adhesive, characterized in that: Including the following ingredients: Modified polyvinyl alcohol powder, deionized water, cross-linking agent, metal salt, inorganic nanoparticles; The amount of inorganic nanoparticles added is 10%-40% of the mass of the modified polyvinyl alcohol powder, and the amount of metal salt added is 0.2-1.2 times the molar amount of acetoacetyl in the modified polyvinyl alcohol powder.

2. An adhesive according to claim 1, characterized in that: The amount of cross-linking agent added is 10%-50% of the mass of the modified polyvinyl alcohol powder.

3. An adhesive according to claim 1, characterized in that: The added amount of modified polyvinyl alcohol powder is 2%-20% of the mass of deionized water.

4. An adhesive according to any one of claims 1 to 3, characterized in that: The modified polyvinyl alcohol powder is acetoacetyl-modified polyvinyl alcohol powder.

5. The adhesive according to claim 1, characterized in that: The cross-linking agent is one of aldehyde compounds, amine compounds and melamine compounds, or a plurality of compounds that do not chemically react with each other.

6. An adhesive according to claim 1, characterized in that: The inorganic nanoparticles are spherical nanoparticles with a particle size of 10nm-100nm.

7. An adhesive according to claim 1 or 6, characterized in that: The inorganic nanoparticles are at least one of spherical nano-silicon dioxide, spherical nano-titanium dioxide, spherical nano-zirconia, spherical nano-zinc oxide and spherical nano-aluminum oxide.

8. The adhesive according to claim 1, characterized in that: The metal salt is at least one of sulfate, chloride and acetate.

9. An adhesive according to claim 1 or 8, characterized in that: The metal cation in the metal salt is Al 3 + Mg 2+ 、Zn 2+ and Zr 4+ 、Ti 4+ At least one of .

10. A method for preparing an adhesive according to any one of claims 1 to 9, characterized in that: The following steps are involved: At a temperature of 20°C-35°C, the modified polyvinyl alcohol powder is added to deionized water, stirred for 0.5h-1h, then the temperature is raised to 85°C-95°C for 1h-5h, and the temperature is kept stirred for 1h-5h; then the temperature is lowered to 20°C-35°C for 5h-15h, a metal salt is added and stirred for 0.5h-2h, a cross-linking agent is added, and stirring is continued for 0.5h-3h, and inorganic nanoparticles are added and stirring is continued for 1h-3h to obtain the adhesive.

11. High weather resistance polarizer, characterized in that: The polarizer comprises an adhesive layer, and the adhesive layer is obtained by coating and curing an adhesive according to any one of claims 1 to 9.